IMMU-43. POLYAMINE METABOLISM REGULATES MYELOID IMMUNE SUPPRESSION IN GLIOBLASTOMA. (11th November 2019) - Miska, Jason; Lee Chang, Catalina; Rashidi, Aida; Han, Yu; Lopez-Rosas, Aurora; Lesniak, Maciej S
Abstract: Tumor-associated myeloid cells, which consist of tumor associated macrophages and myeloid-derived suppressor cells (MDSCs), make up a majority of cellular infiltrates in glioma. Glioma infiltrating MDSCs highly express arginase-1 (Arg-1), a catabolic enzyme thought to deplete arginine from the tumor microenvironment. Despite being a well-known marker of immunosuppressive cells, the metabolic reasons for this choice are not clear. Examination of MDSC phenotype in murine glioma models using: RNA-seq, bulk metabolomics, and Carbon-13 arginine flux revealed that two separate pathways of arginine catabolism converge on the generation of ornithine. Ornithine is the prerequisite substrate for the de-novo generation of polyamines, a group of nitrogen-rich metabolites with foundational importance to all mammalian, bacterial, and plant biology. Importantly, we found that the rate-limiting step of polyamine generation, ornithine decarboxylase 1 (ODC1), is dramatically upregulated by glioma infiltrating MDSCs, suggesting de-novo polyamine generation is important for MDSC function. Treatment with a specific inhibitor of de-novo polyamine synthesis, difluoromethylornithine (DMFO), inhibited the immunosuppressive function of in-vitro generated glioma associated MDSCs. However, DFMO only exerted effects before differentiation, as DFMO treatment post-generation did not change their suppressive functions. This suggests that the generation of the polyamine pool is critical to immune suppression by MDSCs. Interestingly the expression of the rate limiting step of polyamine degradation (SAT1) is inversely correlated with (ODC1) during MDSC differentiation, suggesting that utilization of this polyamine pool may be required for the suppressive functions of these cells. Inhibition of SAT1 after MDSC generation blunted MDSC mediated T-cell suppression. The results of this study show that the role of arginine metabolism in tumor infiltrating MDSCs is to generate pools of polyamines which maintain MDSC function in glioma. Therapeutic targeting of this pathway may be a novel and powerful tool to combat immunosuppression in glioma.